Assessment of Marketing Constraints Perceived by Livestock Owners during the Lumpy Skin Disease Outbreak in Rajasthan - Rajawat, Nirmal Singh; Rajput, Devi Singh; Sharma, Neeraj Kumar; Singodia, Manisha; Meena, Abhishek; Meena, Jyoti (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Lumpy Skin Disease (LSD) has emerged as a major transboundary viral infection affecting cattle, creating substantial economic losses and disruptions in livestock marketing systems. The present study assessed the marketing constraints perceived by livestock owners in five critically affected districts of Rajasthan. High transportation costs, limited vehicle availability, reduced market price of affected cattle, limited digital literacy, and supply chain interruptions emerged as important constraints. Keywords: Constraints, Disease outbreak, Lumpy skin disease, Mean per cent score, Rajasthan.